1993
DOI: 10.1038/bjc.1993.475
|View full text |Cite
|
Sign up to set email alerts
|

p53 immunohistochemistry in transitional cell carcinoma and dysplasia of the urinary bladder correlates with disease progression

Abstract: Summary Immunohistochemically detectable p53 protein using a polyclonal antibody (CM-I) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…However, among patients with superficial TCC its prognostic value is controversial. Using immunohistochemistry, Serth et al [10]found p53 accumulation to be an independent prognostic marker in superficial bladder cancer, and Soini et al [21]reported that p53 accumulation even in dysplasia is a marker of disease progression. Other authors could not confirm those results and denied a correlation between p53 accumulation and patients’ prognosis [11, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among patients with superficial TCC its prognostic value is controversial. Using immunohistochemistry, Serth et al [10]found p53 accumulation to be an independent prognostic marker in superficial bladder cancer, and Soini et al [21]reported that p53 accumulation even in dysplasia is a marker of disease progression. Other authors could not confirm those results and denied a correlation between p53 accumulation and patients’ prognosis [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors therefore use lower cutoff levels. For example, Sarkis et al [24]used a threshold of 5% positive nuclei for detection of p53 overexpression in carcinoma in situ, and Soini et al [21]used 1% positive nuclei as a cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…p53 provides an attractive target for drug action because its inactivation has been shown to be related to disease progression and poor outcome in many types of cancer (Soini et al, 1993;Imamura et al, 1994;Wada et al, 1994;Dšhner et al, 1995;Marks et al, 1996;Dive 1997). On the other hand, p53-dependent apoptosis is known to suppress tumour growth and progression in vivo (Symonds et al, 1994).…”
Section: Cell Line Number Of Positive Cells (%) Amentioning
confidence: 99%
“…Because the inactivation of p53 in cancer has been associated with poor survival, refractory disease and chemoresistance (Lowe et al, 1993;Soini et al, 1993;Marks et al, 1996;Dive 1997), it is conceivable that restoring the function of p53 in cancer cells is worth development in cancer treatment (for a review see e.g. Harris 1996).…”
mentioning
confidence: 99%
“…5 A number of reports have noted that the expression of p53 is correlated with malignancy, tumor progression and poor prognosis. [6][7][8][9][10][11] It is well known that the aberrant expression of EGFR is correlated with bladder cancer progression. [12][13][14][15][16] In this way, it is recognized that this protein is expressed in the majority of bladder carcinomas.…”
mentioning
confidence: 99%